2022
DOI: 10.3390/ijms232113206
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Bladder Cancer: Cell-Free DNA, Epigenetic Modifications and Non-Coding RNAs

Abstract: Bladder cancer (BC) is the 10th most frequent cancer in the world. The initial diagnosis and surveillance of BC require a combination of invasive and non-invasive methods, which are costly and suffer from several limitations. Cystoscopy with urine cytology and histological examination presents the standard diagnostic approach. Various biomarkers (e.g., proteins, genes, and RNAs) have been extensively studied in relation to BC. However, the new trend of liquid biopsy slowly proves to be almost equally effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 139 publications
0
11
0
Order By: Relevance
“…BLCA progression is considered a long-term, multi-step process. Besides genetics, studies have also indicated that epigenetic regulation participates in BLCA progression ( 32 , 33 ). CBX family proteins are important components of epigenetic regulatory complexes and are involved in chromatin modification, and the pathogenesis and progression of a number of tumors ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…BLCA progression is considered a long-term, multi-step process. Besides genetics, studies have also indicated that epigenetic regulation participates in BLCA progression ( 32 , 33 ). CBX family proteins are important components of epigenetic regulatory complexes and are involved in chromatin modification, and the pathogenesis and progression of a number of tumors ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs, such as microRNA (miRNA) and long non-coding RNA (lncRNA), play pivotal roles in gene regulation and biological processes in both health and disease, including cancer initiation and progression. Therefore, they are recognized as potential diagnostic and prognostic markers as well as therapeutic targets for cancers, including bladder UC [ 44 ]. Increasing evidence has indicated that ferroptosis is associated with cancer initiation, progression, and suppression [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several non-invasive urine-based tests have been developed to complement invasive cystoscopy for BC diagnosis utilizing materials in the urine (e.g., urine cytology, BTA, UroVysion, uCyt+, and NMP22) [4][5][6][7]. However, these tests have poor accuracy in detecting BC, with sensitivities between 56% and 83% and specificities between 64% and 88%.…”
Section: Introductionmentioning
confidence: 99%